Seasonal Particulate Matter (PM10) Concentration in Klang Valley, Malaysia - Asmat, Arnis; Norhayati Mohamad Tarmizi, Siti; Hidayah Zakaria, Nur (International Journal of Engineering and Technology, 2018)
This paper presents a study on Seasonal Particulate Matter (PM10) concentration at selected region in Klang Valley for two years database (2002-2004). The study aimed to analyse on how the distribution of PM10 concentration has changed over monsoonal. Kriging method was employed for interpolating PM10 concentration over limited dataset from seven monitoring stations in Klang Valley. Results found that higher PM10 concentration was recorded during Southwest monsoon (65.92Î¼g/m-3) followed by both inter-monsoon (62.17Î¼g/m-3) and (59.13Î¼g/m-3) respectively. Meanwhile, the lowest concentration (36.67Î¼g/m-3) was recorded during northeast monsoon. From the distribution, Klang station has recorded the highest PM10 concentration throughout the season, followed by Kuala Selangor (59.33Î¼g/m-3). Hulu Langat and Gombak stations have shown the lowest concentration of PM10, (40.92Î¼g/m-3) and (36.67Î¼g/m-3) respectively. The spatial distribution map indicated that the PM10concentration level is not only determining by seasonal but also depends on location of monitoring station itself. The concentration may increase if the station is closer to the proximity of urban and industrial pollution sources.Â Â